HUBUNGAN OBESITAS DAN LINGKAR PINGGANG DENGAN KEJADIAN HIPERTENSI TAHUN 2020 - Yunanda Purba, Martha; A. Nababan, Kristo; Burhan (Jurnal Kedokteran Methodist, 2020)
Background: Hypertension is a person said to be hypertensive if his systolic pressure exceeds 140 mmHg and or his diastolic pressure exceeds 90 mmHg. Obesity is being overweight as a result of the accumulation of nutrients, especially carbohydrates, proteins and fats. Waist circumference is a screening measurement method for visceral fat in the body which is associated with an increased risk of metabolic disease. Methods: This research is a research using literature study method or literature review. Data obtained from secondary data using documentation techniques. Data documentation is based on journals related to variables. Conclusion: Based on this research, it is concluded that there is a relationship between obesity and waist circumference with the incidence of hypertension.